Comparative of storage time and prebiotic sources (Inulin and Unripe Banana Flour) on the nutritional content of synbiotic yogurt - Ratih Putri Damayati; Stephani Nesya Renamastika; Firda Agustin; Ayu Febriyatna; Sekar Ayu Wulandari; M. Rizal Permadi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
The consumption of synbiotic yogurt continues to rise; however, Indonesia's reliance on imported inulin as a prebiotic source has also increased by 25.24%. Raw Berlin banana flour (UBF) contains resistant starch that has the potential to serve as a local alternative to inulin. This study aimed to investigate the effects of storage duration and prebiotic sources on the nutritional composition of synbiotic yogurt. A 2 × 3 factorial design was employed, with prebiotic type (Inulin and UBF) and storage time (days 0, 7, and 14) as factors. Each treatment was replicated twice with duplicate analyses. Proximate analyses included moisture, ash, carbohydrate, fat, protein, total energy, and fat energy contents. Data were analyzed using SPSS version 16 with independent t-tests and ANOVA, with significance set at p < 0.05. Results indicated that Storage time significantly affected the moisture, carbohydrate, fat, protein, total energy, and energy from fat contents (p < 0.05). The prebiotic sources inulin and UBF differed significantly in moisture and carbohydrate content on day 7, ash content on day 14, fat and energy from fat on days 0 and 7, and total energy on day 0. In conclusion, both storage duration and prebiotic source influenced the nutritional composition of the synbiotic yogurt.